## Results (1-50 of 88 matches)

Next   displayed columns for results
Label Class Conductor Rank* Torsion $\textrm{End}^0(J_{\overline\Q})$ Equation
169.a.169.1 169.a $$13^{2}$$ $0$ $\Z/19\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^3 + x + 1)y = x^5 + x^4$
196.a.21952.1 196.a $$2^{2} \cdot 7^{2}$$ $0$ $\Z/6\Z\oplus\Z/6\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^2 + x)y = x^6 + 3x^5 + 6x^4 + 7x^3 + 6x^2 + 3x + 1$
324.a.648.1 324.a $$2^{2} \cdot 3^{4}$$ $0$ $\Z/21\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^3 + x + 1)y = x^5 + 2x^4 + 2x^3 + x^2$
676.b.17576.1 676.b $$2^{2} \cdot 13^{2}$$ $0$ $\Z/3\Z\oplus\Z/3\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^2 + x)y = -x^6 + 3x^5 - 6x^4 + 6x^3 - 6x^2 + 3x - 1$
784.c.614656.1 784.c $$2^{4} \cdot 7^{2}$$ $0$ $\Z/2\Z\oplus\Z/2\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 = x^5 - 4x^4 - 13x^3 - 9x^2 - x$
1296.a.20736.1 1296.a $$2^{4} \cdot 3^{4}$$ $0$ $\Z/2\Z\oplus\Z/6\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 = x^5 - x^4 - 3x^3 + 4x^2 - x$
2187.a.6561.1 2187.a $$3^{7}$$ $0$ $\Z/6\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^3 + 1)y = -1$
2704.a.43264.1 2704.a $$2^{4} \cdot 13^{2}$$ $0$ $\Z/2\Z\oplus\Z/2\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 = x^5 - 5x^3 - 5x^2 - x$
2916.a.5832.1 2916.a $$2^{2} \cdot 3^{6}$$ $0$ $\Z/3\Z\oplus\Z/3\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^3 + 1)y = x^3$
3721.a.3721.1 3721.a $$61^{2}$$ $2$ $\mathsf{trivial}$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^3 + x + 1)y = -x^4 + x^3 + 3x^2 + x$
3969.b.35721.1 3969.b $$3^{4} \cdot 7^{2}$$ $2$ $\mathsf{trivial}$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^3 + x + 1)y = -2x^5 + 3x^4 - 3x^2$
3969.c.35721.1 3969.c $$3^{4} \cdot 7^{2}$$ $0$ $\Z/2\Z\oplus\Z/2\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^2 + x)y = x^5 - 5x^4 + 4x^3 - x$
5184.a.46656.1 5184.a $$2^{6} \cdot 3^{4}$$ $0$ $\Z/6\Z$ $$\mathrm{M}_2(\mathsf{CM})$$ $y^2 + x^3y = x^3 + 2$
6075.a.18225.1 6075.a $$3^{5} \cdot 5^{2}$$ $0$ $\Z/6\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^3 + 1)y = x^3 + 1$
8281.b.405769.1 8281.b $$7^{2} \cdot 13^{2}$$ $2$ $\mathsf{trivial}$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^3 + x + 1)y = -3x^5 + 9x^4 - 7x^3 - 2x^2 + x$
8281.c.405769.1 8281.c $$7^{2} \cdot 13^{2}$$ $0$ $\Z/2\Z\oplus\Z/2\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^2 + x)y = x^5 + 8x^4 + 11x^3 + 3x^2 - x$
8649.b.700569.1 8649.b $$3^{2} \cdot 31^{2}$$ $0$ $\Z/2\Z\oplus\Z/2\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^2 + x)y = 9x^5 + 2x^4 - 21x^3 - 22x^2 - 8x - 1$
8649.c.700569.1 8649.c $$3^{2} \cdot 31^{2}$$ $0$ $\Z/2\Z\oplus\Z/2\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^2 + x)y = x^5 + 9x^4 + 13x^3 + 4x^2 - x$
11881.a.11881.1 11881.a $$109^{2}$$ $0$ $\Z/2\Z\oplus\Z/2\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^2 + x)y = x^5 - 3x^4 + 2x^2 - x$
12321.a.36963.1 12321.a $$3^{2} \cdot 37^{2}$$ $2$ $\mathsf{trivial}$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^3 + x + 1)y = x^5 + 3x^4 + 4x^3 + 2x^2$
12544.a.12544.1 12544.a $$2^{8} \cdot 7^{2}$$ $0$ $\Z/2\Z\oplus\Z/2\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 = x^5 + 2x^4 - x^3 - 3x^2 - x$
12544.c.12544.1 12544.c $$2^{8} \cdot 7^{2}$$ $0$ $\Z/2\Z\oplus\Z/2\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 = x^5 - 2x^4 - x^3 + 3x^2 - x$
12544.i.614656.1 12544.i $$2^{8} \cdot 7^{2}$$ $0$ $\Z/2\Z\oplus\Z/2\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 = x^5 + 4x^4 - 13x^3 + 9x^2 - x$
13689.a.13689.1 13689.a $$3^{4} \cdot 13^{2}$$ $2$ $\mathsf{trivial}$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^3 + x + 1)y = x^5 - x^4 - 4x^3 - 2x^2$
13689.b.13689.1 13689.b $$3^{4} \cdot 13^{2}$$ $0$ $\Z/2\Z\oplus\Z/2\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^2 + x)y = x^5 + 3x^4 + x^3 - 2x^2 - x$
15552.c.746496.1 15552.c $$2^{6} \cdot 3^{5}$$ $0$ $\Z/6\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + x^3y = 3x^3 + 8$
15876.b.222264.1 15876.b $$2^{2} \cdot 3^{4} \cdot 7^{2}$$ $0$ $\Z/3\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^3 + x + 1)y = -x^6 + 2x^5 - 4x^4 + 4x^3 - 5x^2 + 2x - 1$
17689.a.17689.1 17689.a $$7^{2} \cdot 19^{2}$$ $0$ $\Z/2\Z\oplus\Z/2\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^2 + x)y = x^5 - 4x^4 + 2x^3 + x^2 - x$
17689.b.17689.1 17689.b $$7^{2} \cdot 19^{2}$$ $2$ $\mathsf{trivial}$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^3 + x + 1)y = -3x^4 - 3x^3 + x^2 + x$
18225.a.18225.1 18225.a $$3^{6} \cdot 5^{2}$$ $1$ $\Z/3\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^3 + 1)y = 1$
20736.a.20736.1 20736.a $$2^{8} \cdot 3^{4}$$ $0$ $\Z/2\Z\oplus\Z/2\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 = x^5 + x^4 - 3x^3 - 4x^2 - x$
20736.f.186624.1 20736.f $$2^{8} \cdot 3^{4}$$ $0$ $\Z/2\Z\oplus\Z/2\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 = x^5 - 2x^4 - 9x^3 - 7x^2 - x$
20736.g.186624.1 20736.g $$2^{8} \cdot 3^{4}$$ $0$ $\Z/2\Z\oplus\Z/2\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 = x^5 + 2x^4 - 9x^3 + 7x^2 - x$
21316.a.42632.1 21316.a $$2^{2} \cdot 73^{2}$$ $2$ $\mathsf{trivial}$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^3 + x + 1)y = 3x^3 + 4x^2 + x$
21904.e.350464.1 21904.e $$2^{4} \cdot 37^{2}$$ $0$ $\Z/2\Z\oplus\Z/2\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 = x^5 + 3x^4 - 11x^3 + 8x^2 - x$
24649.a.24649.1 24649.a $$157^{2}$$ $0$ $\Z/2\Z\oplus\Z/2\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^2 + x)y = x^5 + 4x^4 + 3x^3 - x^2 - x$
26244.c.157464.1 26244.c $$2^{2} \cdot 3^{8}$$ $0$ $\Z/3\Z\oplus\Z/3\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^3 + 1)y = 2x^3$
26244.d.314928.1 26244.d $$2^{2} \cdot 3^{8}$$ $1$ $\Z/3\Z\oplus\Z/3\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + y = x^6 - 2x^3$
26244.e.472392.1 26244.e $$2^{2} \cdot 3^{8}$$ $0$ $\Z/3\Z\oplus\Z/3\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^3 + 1)y = 2$
32761.a.32761.1 32761.a $$181^{2}$$ $2$ $\mathsf{trivial}$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^3 + x + 1)y = x^5 + 10x^2 + 19x + 10$
37636.a.602176.1 37636.a $$2^{2} \cdot 97^{2}$$ $2$ $\mathsf{trivial}$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^3 + x + 1)y = x^5 + 4x^4 + 6x^3 + 3x^2$
38416.a.614656.1 38416.a $$2^{4} \cdot 7^{4}$$ $2$ $\mathsf{trivial}$ $$\mathrm{M}_2(\Q)$$ $y^2 = x^6 - 3x^5 - x^4 + 7x^3 - x^2 - 3x + 1$
43264.c.43264.1 43264.c $$2^{8} \cdot 13^{2}$$ $0$ $\Z/2\Z\oplus\Z/2\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 = x^5 - 5x^3 + 5x^2 - x$
46656.c.93312.1 46656.c $$2^{6} \cdot 3^{6}$$ $1$ $\Z/3\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + x^3y = x^3 - 1$
48841.b.830297.1 48841.b $$13^{2} \cdot 17^{2}$$ $0$ $\mathsf{trivial}$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^3 + x + 1)y = -x^6 + 2x^5 - 5x^4 + 6x^3 - 6x^2 + 2x - 1$
52441.a.52441.1 52441.a $$229^{2}$$ $0$ $\Z/2\Z\oplus\Z/2\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^2 + x)y = x^5 + 5x^4 + 5x^3 - x$
59049.a.177147.1 59049.a $$3^{10}$$ $1$ $\Z/3\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + (x^3 + 1)y = x^3 - 1$
62208.n.746496.1 62208.n $$2^{8} \cdot 3^{5}$$ $0$ $\Z/6\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 = x^6 - 3x^3 + 2$
72900.a.291600.1 72900.a $$2^{2} \cdot 3^{6} \cdot 5^{2}$$ $1$ $\Z/3\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + y = x^6 - 2x^3 + 1$
72900.b.291600.1 72900.b $$2^{2} \cdot 3^{6} \cdot 5^{2}$$ $0$ $\Z/3\Z$ $$\mathrm{M}_2(\Q)$$ $y^2 + x^3y = 2x^3 + 5$
Next   displayed columns for results